Comparação da cinemática do tronco entre as atividades de sentado para de pé e de pé para sentado considerando indivíduos pós-acidente vascular encefálico e saudáveis - Juliane Franco (2019)
Sitting down (stand-to-sit) and standing up (sit-to-stand) from chair are common daily life activities, which are considered essentials for maintaining individual’s mobility and independence. However, investigations related to the sit-tostand are more common than the stand-to-sit, which limits a better understanding of specificity of each activity. Biomechanical descriptions provide a detailed characterization of several aspects of motor control and performance. Thus, accurate detection of movement events is a fundamental step in these assessments. Considering that post-stroke survivors often show lower performance of sit-to-stand and stand-to-sit, it becomes necessary to have a better understanding of the particularities of these activities in these individuals. To obtain the variables of the present study, a study I was developed, in order to compare two different algorithms for the detection of sit-to-stand and stand-to-sit events. The objective of the study II was to compare trunk’s biomechanical characteristics between sit-to-stand and stand-to-sit, at self-selected and fast speeds, considering post-stroke survivors and healthy-matched controls. In the study I, 36 individuals (18 post-stroke/18 healthy, matched by sex, age, body mass index, and levels of physical activity) were included. In the study II, 30 individuals were included, 15 post-stroke/15 healthy-controls, also matched by the same characteristics. Total duration, phase I and II durations, peak of trunk forward flexion and time until the peak of trunk forward flexion of the sit-to-stand and stand-to-sit were determined with the motion analysis system. The results of study I revealed significant differences between the kinematic variables of sit-tostand and stand-to-sit in relation to the different algorithms applied to the data. The algorithm involving the trunk’s center of mass velocity of 0.01m/s was found to be more adequate for the definition of sit-to-stand and stand-to-sit events and, therefore, was used in study II. It was not found any interaction between activities and groups for both speeds (0.17≤F≤0.18; 0.150≤p≤0.164). For both groups and speeds, phase I duration and peak of trunk forward flexion of stand-to-sit activity were significantly higher than of sit-to-stand (4.20≤F≤33.60;0.001≤p≤0.050). For both groups and speeds, phase II duration was significantly higher during the sit-to-stand than during the stand-to-sit (12.20≤F≤65.10;0.001≤p≤0.002). Only at fast speed, the total duration of the stand-to-sit was lower than that of the sit-to-stand, independently of the group (F=8.20; p=0.008). Post-stroke survivors spent more time to complete the entire activity, phase I and phase II durations, than healthy-matched controls subjects at both self-selected and fast speeds, independently of the activity (5.06≤F≤15.38; 0.001≤p≤0.033). Also, the peak of trunk forward flexion and the time spent until the peak of trunk forward flexion were significantly higher in post-stroke survivors when compared to healthy-matched controls at fast speed, for both activities (4.20≤F≤9.61;0.004≤p≤0.050). These results confirm specific biomechanical characteristics between the sit-to-stand and stand-to-sit activities in post-stroke survivors and healthy-matched controls. In addition, these results allow a better understanding of trunk’s specificities between sit-to-stand and stand-to-sit in these populations. Post-stroke survivors showed a worse performance in both activities and at both speeds when compared to healthy-matched controls. Finally, the results reinforce the importance of considering fast speeds during biomechanical evaluations.